Author’s experience in the development of the invention from the aspect of scientific verification and market creation - Žegarac, Nikola P. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The paper presents experiences in the development of inventions, patents and scientific work in terms of scientific verification and marketing. It also describes common problems in the invention development process as well as those regarding invention marketing and introduction to market.